Micronutrient deficiency in the diets of para-athletes participating in a sports scholarship program - Sasaki, C. A. L.; da Costa, T. H. M. (Nutrition, 2021)
Objectives The aim of this study was to determine the usual energy and micronutrient intake distributions and compare the prevalence of insufficient/excessive micronutrient intake in Brazilian para-athletes with and without scholarship support.